PENGARUH PIJAT TERHADAP PRODUKSI ASI PADA IBU POSTPARTUM PRIMIPARA DI KOTA SEMARANG - Agustina Catur Setyaningrum; Melyana Nurul Widyawati (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2018)
One cause of the high failure of breastfeeding was the lack of breastmilk production..Less breastmilk production after giving birth was also possibly caused by the lack of prolactin and oxytocin hormones stimulation. Massage can increase milk production by 11,5 timesThe research aimed to prove the effect of aromatherapic massage toward cortisol level and breastmilk production of primaparous postpartum women in Semarang.Quasy experiment with non equivalent control group design. Sampling technique wasconsecutive sampling. Total samples were 22 persons. To analyze data, Paired Sample Test and Independent Sample T test were used.There was an effect of massageto increased breastmilk production with p value = 0.000. Significant differences of breastmilk production occurred among the all groups (p value = 0,000)and the means different is 40,36 ml. Massage was proven to increase breast milk production in primiparous postpartum .